Pengembangan Media Pembelajaran Kebugaran Jasmani Berbasis Website “Fit & Fun Arena (FFA)” pada Siswa Fase D - Marsely Febiola; Siti Nurrochmah (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
The development of 21st century technology demands the world of education to continue to innovate, including in the learning of Physical Education, Sports, and Health. Physical activity learning that tends to be monotonous and lacks interactive media often leads to a decrease in student interest and motivation to learn. Therefore, this study developed a website-based physical fitness learning media called Fit & Fun Arena (FFA) as a more interesting learning alternative and in accordance with the needs of students. The study used the Research and Development method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were phase D students at SMP Negeri 5 Malang consisting of 5 students in the small group test and 30 students in the large group trial. The validation results showed that the media was in the very valid category, with an assessment of material experts of 98%, learning experts 85%, media experts 91%, and practitioner experts 93%. The small group trial obtained a score of 97% and the large group 92%, so the product was declared very valid. The